Development of Interactive Teaching Modules in Digital Marketing Learning to Improve Vocational High School Students' Learning Outcomes - Sukamto, Dinda Dwi Lukita; Tri Sudarwanto; Yoyok Soesatyo (Jurnal Pendidikan Edutama, 2025)
use of less interactive text teaching modules makes students less enthusiastic and have difficulty in understanding the concept of digital marketing in depth so that it can affect the learning outcomes of these students. This study aims to develop an interactive module in digital marketing learning to improve the learning outcomes of vocational high school students. The research method is Research and Development (R&D) with the ADDIE method type which includes the stages of analysis research (analyze), design stage (design), development stage (development), implementation stage (implementation), and evaluation (evaluation). The interactive module developed contains digital marketing learning materials, interactive evaluations, and multimedia content accessed via Android devices. The results of validation by material experts, language experts, and media experts showed that the interactive module developed was declared very feasible to use. Product trials were conducted on 40 vocational high school students who were divided into two groups, namely the experimental group and the control group. The results of the study showed that the use of interactive modules significantly improved student learning outcomes. The research results show that the use of interactive modules significantly improves student learning outcomes. Furthermore, student responses to the interactive modules were very positive, both in terms of ease of use, appeal, and efficiency. Therefore, these interactive modules are effective in digital marketing learning to improve student learning outcomes.